Correlation Between Nutritional Knowledge and Nutritional Status on Students' Academic Achievement - Fatma Dhafir; Abd. Hakim Laenggen; Masriani Masriani; Lilies Tangge; Rafiqa Rafiqa; Saripa Husnul Qhatimah (Universitas Pendidikan Mandalika, 2025)
This study investigates the relationship between nutritional knowledge, nutritional status, and academic achievement among junior high school students. Nutrition plays a vital role in cognitive performance, influencing concentration, memory, and energy levels. A cross-sectional correlational study was conducted at SMP Negeri 14 Palu, Central Sulawesi, involving 60 students across grades VII to IX. Data were collected using a structured questionnaire, anthropometric measurements, and academic performance records. Bivariate analysis using the Gamma correlation test revealed a statistically significant positive relationship between nutritional knowledge and academic achievement (Gamma = 0.515; p = 0.003). Conversely, a significant negative correlation was observed between nutritional status and academic performance (Gamma = –0.543; p = 0.040). These findings underscore the importance of structured nutrition education in supporting academic outcomes, while also highlighting the complex, non-linear relationship between physical health indicators and cognitive performance.